Leading issues in economic development - Meier, Gerald M.; Rauch, James E. (New York : Oxford University Press, 2005)
Completely updated and revised in this eighth edition, Leading Issues in Economic Development provides extensive coverage of the most pressing debates in the field through professional journal articles by leading scholars. Carefully edited for an undergraduate audience, the articles are organized thematically and supplemented by overview essays, explanatory notes, and comments by the editors. This distinctive approach allows for a variety of perspectives while maintaining focus on the most important overarching themes."--Jacket
Includes bibliographical references and index.
Keywords: Economic development -- Textbooks